2007
DOI: 10.4269/ajtmh.2007.77.1054
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Molecular Tool for the Identification of Leishmania Reservoir Hosts by Blood Meal Analysis in the Insect Vectors

Abstract: The transmission of parasites of the genus Leishmania involves a large diversity of mammalian reservoir hosts. However, many of these are yet to be identified, mainly in isolated biotopes such as the Amazonian rain forest. Furthermore, the trophic preferences of insect vectors have major epidemiologic implications. In this study, we developed a molecular tool for the identification of blood meals of phlebotomine sand flies. This assay is based on specific amplification and sequencing of the blood meal-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
1
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 43 publications
8
76
1
6
Order By: Relevance
“…Therefore, it is probable that MVV is transmitted by sandfly species of the subgenus Larroussius. A similar study performed in a rural setting in Tunisia showed that P. perniciosus feed mostly on cattle (92 %) and less on humans (4.5 %), and therefore this sandfly species is highly zoophilic (Haouas et al, 2007). However, in urban and peri-urban areas, where sandfly females become deprived of livestock, they may adapt to bite humans and dogs more frequently (Rossi et al, 2008).…”
Section: Microneutralization Assaysmentioning
confidence: 81%
“…Therefore, it is probable that MVV is transmitted by sandfly species of the subgenus Larroussius. A similar study performed in a rural setting in Tunisia showed that P. perniciosus feed mostly on cattle (92 %) and less on humans (4.5 %), and therefore this sandfly species is highly zoophilic (Haouas et al, 2007). However, in urban and peri-urban areas, where sandfly females become deprived of livestock, they may adapt to bite humans and dogs more frequently (Rossi et al, 2008).…”
Section: Microneutralization Assaysmentioning
confidence: 81%
“…The fragment fulfilled the requirement of relatively short size and enough sequence divergence to achieve objectives of the study. It is therefore likely to find a sequence entry of an unknown sample or at least of a related species [3] . Moreover, cytb has been widely used in identifying blood meal due to their high copy numbers and sufficient genetic variation at the primary sequence level among vertebrate taxa [17,23] .…”
Section: Discussionmentioning
confidence: 99%
“…It is a challenge to conduct subsequent examination of the host's efficiency to transmit infectious agent to the vector organisms under controlled condition [2] . Moreover, such laboratory-based estimates may fail to capture the true distribution of host competencies because of unknown consequences of host selection behavior by vector organisms or the unmeasured contributions of cryptic reservoir hosts [3,4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, thestudy of blood meal sources of vectors plays an essential role.Accordingly, serological techniquesas ELISA were appliedas first approachin this way (De Colmenares et al 1995, Bongiorno et al 2003, although these methods have been replaced by molecular tools for their better accuracy (Mukabana et al 2002, Haouas et al 2007, Kent 2009,Maleki-Ravasan et al 2009). Amplification by polymerase chain reaction (PCR) and subsequent sequencingis widely used to study bloodmeal preferences in sand flies and other vectors as mosquitoes or ticks (Kirstein and Grey 1996, Oshagi et al 2006, Danabalan et al 2014.Thus, different molecular targets like cytochrome b (cytb), cytochrome oxidase I (COI) and prepronociceptin (PNOC) are being used to detect the origin of blood meals (Kocher et al 1989, Haoaus et al 2007, Abassi et al 2009).…”
Section: Introductionmentioning
confidence: 99%